Risk Identification Activities Warehouse using Fuzzy AHP and Fuzzy FMEA Method - Albab, Garnisa Ikwanus Sofa Ullul; Supriyadi, Supriyadi; Nalhadi, Ahmad; Shofa, Mohamad Jihan; Maharani, Ardita (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2023)
Warehouse is an important part of a company’s supply chain. The supply chain of a company involves various stages of activity, including the inspection stage, product¬ion stage, marketing stage, material handling stage, and finished product stage. Problems that occur related to the handling of poor product processes have an impact on the loading process and product delivery to consumers. Resolution methods from the literature can use AHP, FMEA, Fuzzy FMEA, and Fuzzy AHP-FMEA. This research tries to integrate Fuzzy AHP and Fuzzy FMEA to get a priority ranking of risk levels and provide recommen¬dations for decisions in warehouse management. The use of fuzzy in both methods because both methods use expert opinion and fuzzy can minimize the bias value of each respondent. The result of the research is a recommendations for the priority order of improvement of various potential risks that occur in the warehouse.